Similarities and differences between molecular order in the nematic and twist-bend nematic phases of a symmetric liquid crystal dimer. Issue 14 (16th March 2016) - Emsley, J. W.; Lelli, M.; Joy, H.; Tamba, M.-G.; Mehl, G. H.
Abstract : Carbon-13 chemical shift anisotropies reveal an unusual temperature dependence of the order parameters, S zz, for the difluoroterphenyl groups in the normal nematic, N and the twist-bend nematic, NTB, phases. Abstract : The order parameter, S zz, where z is the para axis of the difluoroterphenyl groups in DTC5C9, has been obtained from chemical shift anisotropies measured by 13 C – { 1 H} NMR experiments at temperatures throughout the nematic, NU, and twist-bend nematic, NTB, phases shown by this compound. The order parameter temperature profiles are unusual in having a maximum value in the NU phase and then decreasing until the NTB phase is reached. There is a small discontinuity (∼2%) in S zz at T NNTB and then a gradual decrease until a new phase appears. This behaviour is interpreted as revealing a temperature-dependent tilting of local directors in both phases away from the applied magnetic field direction. In the enantiomorphic twist-bend phase this tilt is consistent with the structure of the phase as a helical arrangement of local directors, whilst in the high-temperature non-chiral nematic the tilt must involve a non-chiral arrangement. It is proposed that in both phases the tilting of directors has a common origin in the bent shape of the molecules.